Hydropower and climate change, insights from the integrated water-energy modelling of the Drin Basin - Youssef Almulla; Klodian Zaimi; Emir Fejzić; Vignesh Sridharan; Lucia de Strasser; Francesco Gardumi (Energy Strategy Reviews, 2023)
The understanding of the transboundary impact of Climate Change on hydropower is not well-established in the literature, where few studies take a system perspective to understand the relative roles of different technological solutions for coordinated water and energy management. This study contributes to addressing this gap by introducing an open-source, long-term, technologically-detailed water and energy resources cost-minimisation model for the Drin River Basin, built in OSeMOSYS.The analysis shows that climate change results in a 15–52% annual decline in hydro generation from the basin by mid-century. Albania needs to triple its investments in solar and wind to mitigate the risk of climate change. Changing the operational rules of hydropower plants has a minor impact on the electricity supply. However, it can spare significant storage volume for flood control.